Implementation of Madrasah Head Supervision in Increasing Teacher Work Productivity - Arham, Arham; Supriadi, Supriadi; Firmansyah, Firmansyah; Hasbullah, Hasbullah (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study aims to find out: Supervision ofÂ Madrasah Heads at MTs Baytul Mukarromah, Work Productivity of Teachers at MTs Baytul Mukarromah, Implementation of Supervision of Madrasah Heads in Increasing Teacher Work Productivity at MTs Baytul Mukarromah. To obtain data from these problems, the author uses qualitative field research methods with data collection techniques, namely observation, interviews and documentation. The results of the study show that the supervision of the head of the madrasah at MTs Baytul Mukarromah is good. This is in accordance with the analysis of interview data that the existence of supervision in madrassas is good and very meaningful because it has an important role so that the madrassas can be monotonous. And the productivity of the teacher's work, each teacher in the field of study understands exactly what we have to do, sometimes how to understand that I am not just walking in the place, which means that there must be improvements and improvements to achieve the so-called educational goals themselves. As well as the method used in supervising the teacher's work by making observations.